Anti‐PD‐1 Immunotherapy‐Induced Flare of a Known Underlying Relapsing Vasculitis Mimicking Recurrent Cancer. (14th May 2019) - Nabel, Christopher S.; Severgnini, Mariano; Hung, Yin P.; Cunningham‐Bussel, Amy; Gjini, Evisa; Kleinsteuber, Katja; Seymour, Lake J.; Holland, Martha K.; Cunningham, Rachel; Felt, Kristin D.; Vivero, Marina; Rodig, Scott J.; et al.
Abstract: : Safe use of immune checkpoint blockade in patients with cancer and autoimmune disorders requires a better understanding of the pathophysiology of immunologic activation. We describe the immune correlates of reactivation of granulomatosis with polyangiitis (GPA)—an antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis—in a patient with metastatic urothelial carcinoma treated with pembrolizumab. After PD‐1 blockade, an inflammatory pulmonary nodule demonstrated a granulomatous, CD4+ T‐cell infiltrate, correlating with increased CD4+ and CD8+ naïve memory cells in the peripheral blood without changes in other immune checkpoint receptors. Placed within the context of the existing literature on GPA and disease control, our findings suggest a key role for PD‐1 in GPA self‐tolerance and that selective strategies for immunotherapy may be needed in patients with certain autoimmune disorders. We further summarize the current literature regarding reactivation of autoimmune disorders in patients undergoing immune checkpoint blockade, as well as potential immunosuppressive strategies to minimize the risks of further vasculitic reactivation upon rechallenge with anti‐PD‐1 blockade. Key Points: Nonspecific imaging findings in patients with cancer and rheumatological disorders may require biopsy to distinguish underlying pathology. Patients with rheumatologic disorders have increased risk of reactivation with PD‐(L)1 immune checkpoint blockade, requiring assessment of disease status before starting treatment. Further study is needed to evaluate the efficacy of treatment regimens in preventing and controlling disease reactivation. Abstract : Immune checkpoint blockade can come with the cost of toxicities induced by an activated immune system that damages normal tissues. This article presents the cautionary case of a patient with granulomatosis with polyangiitis that was exacerbated by administration of pembrolizumab.